Primary Cilia and Atherosclerosis - Wang, Zhi-Mei; Gao, Xiao-Fei; Zhang, Jun-Jie; Chen, Shao-Liang (Frontiers in Physiology, 2021)
In artery tree, endothelial function correlates with the distribution of shear stress, a dragging force generated by flowing blood. In laminar shear stress areas, endothelial cells (ECs) are available to prevent atherosclerosis, however, ECs in disturbed shear stress sites are featured with proinflammation and atherogenesis. Basic studies in the shear stress field that focused on the mechanosensors of ECs have attracted the interest of researchers. Among all the known mechanosensors, the primary cilium is distinctive because it is enriched in disturbed shear stress regions and sparse in laminar shear stress areas. The primary cilium, a rod liked micro-organelle, can transmit extracellular mechanical and chemical stimuli into intracellular space. In the cardiovascular system, primary cilia are enriched in disturbed shear stress regions, where blood flow is slow and oscillatory, such as the atrium, downstream of the aortic valve, branches, bifurcations, and inner curves of the artery. However, in the atrioventricular canal and straight vessels, blood flow is laminar, and primary cilia can barely be detected. Primary cilia in the heart cavity prevent ECs from mesenchymal transition and calcification by suppressing transforming growth factor (TGF) signaling. Besides, primary cilia in the vascular endothelium protected ECs against disturbed shear stress-induced cellular damage by triggering Ca2+ influx as well as nitric oxide (NO) release. Moreover, primary cilia inhibit the process of atherosclerosis. In the current review, we discussed ciliogenesis, ciliary structure, as well as ciliary distribution, function and the coordinate signal transduction with shear stress in the cardiovascular system.